Epidemics and diseases in Africa: Epidemics and diseases in Africa (jornal of the libyan geographical society, 2009)
The climate was linked to those long-standing negative phenomena that the African continent, especially equatorial Africa, was a continent plagued by endemic diseases. The unhealthy climate was the reason why West Africa was known as the graveyard of the white man, and many parts of the African continent are still referred to as the continent of endemic diseases.  Compared to some other places on the continent, such as the Kenyan highlands, which were settled by Europeans in search of mineral wealth, this is due to the direct impact of climate on the normal, healthy functioning of the population.The impact of climate on productive human activity varies in different parts of the world, but not to the degree or extent that the white man has caused in tropical Africa. The dangers and climatic difficulties of life in some parts of it are not directly due to the climate, but to the many diseases prevalent in the continent.The diseases that afflict both humans and animals are numerous, severe, and often fatal. Although some of their causes are now understood, overcoming them requires dedicated care and resources.
Keywords: Climate; African continent; Continent of endemic diseases; Health and functional performance of the population